Letter (copy) : Help for the Workers of Spain Fund - Citrine, Walter, 1887-1983
028-0200-001 JWP/HB/MH WMC/FEM/KMS/590. Secretary's. 5th September, 1936. Mr. J.W. Prestwich, Co-operative Wholesale Society, Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Prestwich, HELP FOR THE WORKERS OF SPAIN FUND. I am in receipt of your personal letter of the 3rd September, notifying us that your Directors have decided to make a grant of £200 guineas forthwith to help the workers of Spain. I note that your shareholders at their October meeting will be asked to confirm this action. The grant you are making will be very much appreciated by the sponsors of the Fund. As you will have soon from the recent news the need in Spain is very great indeed. Yours sincerely, General Secretary. P.S. Your cheque can be made out to the Trades Union Congress. 292/946/28/200